(3CQHYhf MOjKkGs - (3CMeO Hf MSjf Hf eUWai GdcQjOjs; (3GdefPQj , YHO GdYXje Hf YHO Gdbhj Hf YHO Gddg, Rcj GdOjf CHh eMeO,J (B656 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdabjQ Edi Gddg GdgGOj CMeO GHf MSjf GHf eUWai GdcQjOi gPg CQHYhf EfJNHJgG ef JQZjH GdMGaX YHOGdYXje GdefPQi s
(3BNQgG (B:s
(3hGMaX dSGfc adQHeG GdEfSGf ef jfOe hUdi Gddg Ydi SjOfG hfHjfG eMeO hYdi Bdg hCUMGHg hPQjGgBejf jGQH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs